Length-weight relationships for nine species of batoids from the Iskenderun Bay, Turkey - Basusta, A.; Basusta, N.; Sulikowski, J. A.; Driggers, W. B., III; Demirhan, S. A.; Cicek, E. (Wiley-Blackwell, 2012)
Presented are lengthweight relationships for Rhinobatos rhinobatos, Rhinobatos cemiculus, Gymnura altevela, Dasyatis pastinaca, Rhinoptera marginata, Pteromylaeus bovinus, Torpedo nobiliana, Raja miraletus and Raja clavata captured by gillnet, longline and bottom trawl fishing between May 2010 and July 2011 off the east coast of Iskenderun Bay, Turkey.
Keywords: Rhinobatos-Rhinobatos; Common Guitarfish